MIND-OUT: Medications in Intensive Care, Delirium and OUTcomes - Hannah Reynolds; Bhamini Patel; Sara Ormerod; Felicity Evison; William Tunnicliffe (BJPsych Open)
Aims: To investigate how anticholinergic burden of medications changes during hospital stay for Intensive Care Unit (ICU) patients and to review whether anticholinergic burden predicts delirium and mortality.